Variation in Germination of Dalbergia sissoo Roxb. Seeds under Different Media and Osmoconditions - Sagta, H.C.; Nautiyal, S. (Indian Forester, 2001)
The effect of media and osmocondition on seed germination was investigated in Dalbergia sissoo Roxb. at nursery condition. Seeds were sown at 1 cm depth in plastic trays in 5 different media viz. coconut husk, garden soil, white quartz sand, sawdust and vermiculite. These media were maintained in 4 different osmoconditions (control, -0.118 atm., -0.353 atm and -1.235 atm) by the application of polyethylene glycol (PEG). The highly significant variation (P<O.Ol) was observed within the effect of media, osmocondition and their two-factor interaction for germination percentage, germination value and mean germination time. Seeds under control watering in sawdust delineate highest germination percentage, germination value and minimum mean germination time, followed by the quartz sand under control watering. While minimum germination percentage, germination value and maximum mean germination time was observed for coconut husk under lower osmotic potential. The low osmocondition can check the germination per cent, germination value and increase the mean germination time of Dalbergia sissoo seeds. It is recommended that sawdust and white quartz media under normal watering at nursery condition are better for germination of Dalbergia sissoo seeds.